Impact Evaluation of Skill Acquisition and Entrepreneurial Development Training Programmes in Ondo State, Nigeria (2004)
The Ondo State government established two programmes in 1999 under two different ministries with the view of providing the people with entrepreneurial and vocational skills that would engender creativity, innovativeness and productivity. Extant literature on the effectiveness and success of these programmes has been self-reporting without any empirical validation. This study, therefore, was carried out on the impact evaluation of the skill acquisition (SATP) and entrepreneurial development training programmes (EDTP) between 1999 to 2009 in Ondo State, Nigeria. The descriptive survey research and Kirkpatrick training evaluation model (KTEM) were adopted. A combination of purposive stratified and proportional sampling techniques were used to select 1080 participants: 720 current trainees and 360 graduates of the two training programmes. Two instruments were used: Skill Acquisition Training Questionnaire (r=0.86) and Entrepreneurial Development Training Programme Scale (r=0.79). These were complemented with 18 sessions each of Focus Group Discussion and indepth interview respectively with trainees and instructors respectively. Eight hypotheses were tested at p<0.05 level of significance. Data were subjected to chi-square, Pearson’s product moment correlation, t-test and content analysis. Skill acquisition (χ²=78.12,) and entrepreneurial development (χ² =56.40,) training programmes impacted positively on the beneficiaries. The SATP (r=0.37) had low positive correlations with encouragement of adoption of local technology while EDTP did not. Both SATP (r=0.27) and EDTP (r=0.24) correlated positively with enhancement of peace and stability. The SATP (r=0.59) stimulated the interest of the youths in vocational trades than EDTP (r=0.28). The EDTP (r= 0.24) provided more encouragement for productive entrepreneurial and acquisition of small business management skills than SATP (r=0.58). Both SATP (r=0.24) and EDTP (r=0.24) provided positive encouragements for self-employment for self-reliance among trainees. The two programmes fairly impacted on the beneficiaries majorly because of low awareness, inaccessibility, poor funding and politicizing of the programmes. Further, the general effectiveness level of the programmes based on KTEM revealed that: SATP was very positive (61.0%) to participants’ reactions to the training programme while EDTP was positive (48.0%). On increase in knowledge and skill, SATP was very positive (67.0%) while ADTP was below average (43.0%). Both programmes were relatively positive on the participants: application of acquired knowledge and skills. Also, SATP was fairly positive (53.0%) while ADTP was positive: Tangible results of training: SATP was fairly positive (59.0%), while ADTP was very positive (40.0%); on the investment return on training, SATP was very positive (66.0%) while EDTP was positive (40.0%). Participants perceived that the training programmes had challenges of accessibility, poor funding, unconducive environment and political maneuverings. Skill acquisition and entrepreneurial development training programmes impacted not too positively on the beneficiaries. There is the need to make skill acquisition and entrepreneurial development training programmes more accessible to the citizens